Vulnerability of Housewives to HIV Transmission: A Picture of Risky Sexual Behavior - Takariningsih Dwi Narwiyanti; Rofiq Damayanti; Noer Soelistyaningsih (Jurnal EduHealth, 2025)
A 2023 survey in East Java reported a 1% HIV positive rate among pregnant women. Data from the East Java Provincial Health Office also shows an increase in reported HIV cases among women. One of the reasons that causes women to be included in the vulnerable group for contracting HIV/AIDS is because their husbands or sexual partners engage in unsafe sexual behavior outside of marriage. Women's vulnerability to the transmission of diseases such as HIV/AIDS is based on several factors that occur at the individual, household, and community levels as well as the macro level that often makes women unaware of the dangers of HIV/AIDS. There is still little research describing how women are at risk of contracting HIV/AIDS. This study aims to analyze women's exposure to HIV/AIDS associated with risky sexual behavior. This qualitative study used an in-depth interview method with a semi-structured interview guide with 25 informants consisting of female informants, male informants, counselors and providers. health services at three service locations in East Java. Data were validated using member checking and peer debriefing techniques, then analyzed thematically. Risk behaviors that put women at risk of HIV/AIDS transmission were identified in men, including having sex with more than one sexual partner, bisexuality, purchasing sex, and inconsistent condom use. Meanwhile, risk behaviors among women included having more than one sexual partner, having a lower bargaining position in condom negotiations, prostitution, and forced sex.